Hydrophilicity‐Hydrophobicity Transformation, Thermoresponsive Morphomechanics, and Crack Multifurcation Revealed by AIEgens in Mechanically Strong Hydrogels. Issue 39 (4th August 2021) - Hu, Yubing; Barbier, Lucile; Li, Zhao; Ji, Xiaofan; Le Blay, Heiva; Hourdet, Dominique; Sanson, Nicolas; Lam, Jacky W. Y.; Marcellan, Alba; Tang, Ben Zhong
Abstract: Biomimetic exploration of stimuli‐responsive and crack‐resistant hydrogels is of great academic and practical significance, although the rational design of tough hydrogels is limited by insufficient mechanism study due to the lack of imaging techniques to "see" hydrogels at mesoscale level. A series of composite hydrogels with compartmentalized thermal response is designed by incorporating aggregation‐ and polarity‐sensitive fluorescent probes in a poly( N ‐isopropylacrylamide) (PNIPAM) network grafted with poly( N, N ‐dimethylacrylamide) side‐chains. The fluorescence technique is explored as a powerful tool to directly visualize their hydrophilicity‐hydrophobicity transformation and the composition‐dependent microphase separation. Based on the morphological observation and mechanical measurements, the concept of morphomechanics with a comprehensive mechanism clarification is proposed. In this regard, the thermoresponsive toughening is attributed to the formation of multiple noncovalent interactions and the conformational changes of PNIPAM chains. The enhanced fracture energy by crack multifurcation is related to the tearing‐like disruption of weak interfaces between the separated phases. Abstract : The direct visualization of microphase separation and easy differentiation of hydrophilicity–hydrophobicity transformation is achieved in a facile, high‐contrast, and noninvasive manner by using luminogens with aggregation‐induced emission as fluorescent indicators. Based on the morphological observation and mechanical study, the concept of morphomechanics with a comprehensive mechanism clarification is proposed.